(untitled) (Research, Society and Development, 2021)
The use of technology systems at the health area has been an excellent tool in improving the care assistance to the patient/client, as it allows the professional to collect, record data and communicate with the multiprofessional team more quickly and effectively. This is a descriptive type methodological study, with the objective of showing the development of a prototype of a mobile application of medium fidelity for the Nursing Process of the renal patient. The prototype is composed by 29 screens and was built with the intention of offering a hospital service the application of the Nursing Process quickly, accurately and safely. In general, the construction of the screens was divided into categories: home screen, login menu, hospital registration, hospital menu, collaborative registration, collaborative login, patient menu, patient registration, process options, nursing history, physical examination, suggested diagnoses, selected diagnoses, care plan, expected results, implementation, evaluation, complications, patient’s destination and previous records. From this study, it became feasible to build a mobile application prototype to perform the nursing process focused on the chronic kidney patient, this prototype will serve as an instrument for further studies, with the necessary adjustments to achieve the desired result.